Digitization of the DNA-Forensic Analysis Laboratory NSRI-UPD resource materials - Viray, Dianne Angela C. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
In today's society, digitization has proven to be beneficial for information centers in many ways particularly in the academe. Digitization is defined as a process of converting analog materials into an electronics format using the scanner, computer and other electronic devices in order to, in many cases, provide users wider access to such materials. Besides this, the DNA Analysis Laboratory (DAL), NSRI-UPD also embarked on this project to strategize the digitization of its in-house library collection.